Massive hemoptysis bridged with VV ECMO: A case report - Ryan, Dylan; Miller, Kathleen; Capaldi, Carly; Pasquarello, Claudine; Yang, Qiong; Hirose, Hitoshi (Frontiers in Cardiovascular Medicine, 2022)
Objective: Extracorporeal membrane oxygenation (ECMO) can provide full pulmonary support when a patient is completely apneic. The combination of veno-venous (VV) ECMO and induced apnea can be utilized to control significant hemoptysis. We present a case of massive hemoptysis that developed while on VV ECMO and was treated with temporary discontinuation of the ventilator and serial de-clotting bronchoscopies. Methods: A 42-year-old male with recent acute myocardial infarction status post cardiac stent developed aspiration pneumonia that progressed to acute respiratory distress syndrome. The patient’s biventricular function was preserved. VV ECMO was placed for lung rescue on hospital day #7 and tracheostomy was performed for ventilator dependence on hospital day #12. On hospital day #18, the patient developed significant hemoptysis despite the discontinuation of anticoagulation. Bronchoscopy revealed massive bleeding from bilateral bronchi. To facilitate tamponade within the tracheobronchial tree, the ventilator was briefly discontinued while VV ECMO provided full respiratory support. After 48 hours, mechanical ventilation was resumed and daily bronchoscopies were performed to remove clots from both bronchi until chest x-ray showed improvement in bilateral opacifications. Bronchoscopy was performed a total of 14 times. There was no recurrence of bronchial bleeding, the patient’s respiratory status improved, and VV ECMO was weaned off on hospital day #37. The patient was transferred to a long-term rehabilitation facility 36 days after successful ECMO decannulation on hospital day #73. Conclusions: This patient’s survival of massive hemoptysis was facilitated largely by the utilization of serial de-clotting bronchoscopies with VV ECMO providing full pulmonary support during temporary discontinuation of mechanical ventilation.